Influence of corrugation angle in the stirred yoghurt processing in plate heat exchangers - Fernandes, Carla S. (2004)
Research on heat transfer of non-Newtonian fluids during thermal processing is very useful for optimise heat exchanger design, as well as to define quality levels of the final product. In the present study non-isothermal, non-Newtonian flow in plate heat exchangers were simulated numerically, in order to evaluate the influence of corrugation angles on the thermal and hydrodynamics characteristics of yoghurt cooling in a plate heat exchanger. Simulations were carried out using the commercial finite element method package POLYFLOW, being the geometrical domain the representation of a single 3D channel of the plate heat exchanger. Two corrugation angles were considered, 30º and 60º, being the obtained numerical results for the first one compared with experimental data. A laminar flow was observed for the two cases and the decrease of the angle conducted to a decrease of pressure drop and maximum shear rate.